OPTIMIZATION OF DIGITAL MEDIA AS A MEANS OF STRENGTHENING ENGLISH LANGUAGE SKILLS AND BUSINESS MANAGEMENT AMONG MSME ACTORS - Vivi Asbar; Fajrinur; Laina Fadhilah (Jurnal Pengabdian Bangsa, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in economic development but often face limitations in digital literacy, English language proficiency, and basic business management, which reduce their competitiveness in the digital era. This community service program aimed to optimize digital media as an integrated platform to strengthen practical English skills and business management competencies among MSME actors. The program employed a participatory and practice-oriented approach consisting of training, hands-on practice, and continuous mentoring. Training activities focused on functional English for business communication, digital media utilization for marketing, and basic management practices such as branding and simple bookkeeping. The results indicate improvements in participants’ ability to use English for product promotion, increased use of digital media for marketing activities, and greater awareness of structured business management. Participants also showed higher engagement and confidence in applying digital tools to their daily business operations. These findings suggest that integrated digital media–based capacity building is effective in supporting MSME empowerment and sustainable economic development.